Pregnancy-induced pituitary apoplexy: Two lives at stake - Izhar Faisal; Teshi Kaushik; Pragati Ganjoo; Anita Jagetia (Wolters Kluwer Medknow Publications, 2023)
Pituitary apoplexy in a pregnant woman is a devastating condition that develops secondary to a massive increase in the size of the pituitary gland and hyperplasia of lactotroph cells caused by high estrogen levels of pregnancy. The resultant sudden hemorrhage or infarction into the pituitary gland or a tumor leads to gland destruction with serious consequences like acute adrenal insufficiency, circulatory shock, neurological deterioration, and visual loss. Prompt handling of complications is necessary to prevent maternal and fetal mortality. Resuscitation is aimed at the early correction of hemodynamic instability, fluid-electrolyte abnormalities, hormone deficiencies, and intracranial hypertension. Urgent decompressive pituitary surgery may be required if the patient has rapidly declining vision and neurological status. Management of such patients is challenging and requires multi-disciplinary collaboration. We describe here the emergency handling of pituitary apoplexy in a pregnant woman.